2018
DOI: 10.1002/cche.10009
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating effect of calcium and magnesium on acrylamide formation in tortilla chips

Abstract: Background and objectives: The effectiveness of calcium and magnesium, as CaCl 2 and MgCl 2 , respectively, to reduce acrylamide formation in tortilla chips fried in soybean oil during 30 s at 190°C was evaluated. Findings: Acrylamide was reduced 69%, 70%, and 74% by adding 0.04, 0.08, and 0.12 M of MgCl 2 solutions to prepare the masa, compared with the reductions in 52%, 67%, and 52% obtained using 0.04, 0.08, and 0.12 M of CaCl 2 , respectively. The color, oil absorption, and the fracture force of tortilla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Worldwide, in recent years many new methods have been developed for the determination of AA in food products, such as: high performance liquid chromatography mass spectrometry (HPLC–MS), high performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS), gas chromatography-electron capture detection (GCECD), gas chromatography-mass spectrometry (GC-MS), liquid chromatography (LC) with ultraviolet (UV), or MS detection, and capillary electrophoresis (CE) with UV and MS, [ 22 , 24 , 56 , 68 , 69 , 70 ], solid-phase extraction (SPE) (were used to analyze acrylamide in bread), and dispersive liquid-liquid microextraction (DLLME) [ 71 ]. The ultra-performance liquid chromatography (UPLC) method has the advantage that the resolution is improved with higher analytical sensitivity and a shorter retention time [ 72 ].…”
Section: Legislative Rules On the Maximum Benchmark Levels Of Acrylamide In Bakery Productsmentioning
confidence: 99%
“…Worldwide, in recent years many new methods have been developed for the determination of AA in food products, such as: high performance liquid chromatography mass spectrometry (HPLC–MS), high performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS), gas chromatography-electron capture detection (GCECD), gas chromatography-mass spectrometry (GC-MS), liquid chromatography (LC) with ultraviolet (UV), or MS detection, and capillary electrophoresis (CE) with UV and MS, [ 22 , 24 , 56 , 68 , 69 , 70 ], solid-phase extraction (SPE) (were used to analyze acrylamide in bread), and dispersive liquid-liquid microextraction (DLLME) [ 71 ]. The ultra-performance liquid chromatography (UPLC) method has the advantage that the resolution is improved with higher analytical sensitivity and a shorter retention time [ 72 ].…”
Section: Legislative Rules On the Maximum Benchmark Levels Of Acrylamide In Bakery Productsmentioning
confidence: 99%
“…For example, the use of MgCl 2 as a divalent cation in masa preparation was reported as an effective mitigation strategy in tortilla chips with a reduction of acrylamide by 69–74% depending on the concentration of the salt used. Similarly, the use of CaCl 2 in masa preparation reduced acrylamide by 52% to 67% in tortilla chips . Adding asparaginase to masa reduced the acrylamide in tortilla chips by 90% .…”
Section: Acrylamide Mitigation Strategies In Corn-based Food Productsmentioning
confidence: 96%
“…Similarly, the use of CaCl 2 in masa preparation reduced acrylamide by 52% to 67% in tortilla chips. 84 Adding asparaginase to masa reduced the acrylamide in tortilla chips by 90%. 85 Another study showed that the addition of the amaranth protein isolate to the recipe of masa decreased the acrylamide content by 51% and 62% in fried tortilla chips and baked tortilla chips, respectively.…”
Section: Acrylamide Mitigation Strategies In Corn-based Food Productsmentioning
confidence: 99%